Distribution of genotypes C825T polymorphism G-protein β3-subunit gene in patients with hypertension depending on body mass index - Prystupa L.N.; Moisejenko I.O. (Medičnì Perspektivi)
The aim of the study was to investigate the frequency of genotypes of C825T polymorphism G-protein β3-subunit gene (GNB3) in patients with arterial hypertension (AH), depending on body mass index (BMI). The study involved 155 patients with verified diagnosis of AH (study group) and 50 healthy individuals (control group). The patients of the main group were divided into 3 groups according to BMI: I - 35 patients with normal body weight, II - 38 patients with overweight, III - 82 patients with obesity. We used general clinical, anthropometric, instrumental, molecular-genetic and statistical methods. Probability of differences in the frequency of alleles and genotypes was determined using χ² criteria. Pairwise comparison of groups was made using nonparametric Mann-Whitney test. The difference was considered statistically significant at p <0,05. Investigation of the distribution of genotypes C825T polymorphism GNB3 in patients with AH according to BMI showed statistically significant increase in the frequency of genotypes C / T and T / T and T allele in patients with overweight and obesity as compared with patients with normal body weight (χ² = 26 8; p <0.001). The risk of weight increase in AH patients with T allele carriers is 2,2 times higher than in C allele carriers. Association of C825T polymorphism of GNB3 with a tendency to obesity and overweight in patients with AH was proved.